Georgia Architectural and Historic Properties Survey of 508, 509, and 510 Third Ave., Valdosta (Ga.), 1980-1981 - Smith, Bartholomew; Smith, Freda (South Georgia Area Planning and Development Commission, 1980)
va47-f01_02-va47-f01_04: 508, 509, 510 Third Ave. Valdosta, GA. Three shotguns with tin gabled roof, clapboard and shiplap siding. Exposed rafters. Interior chimneys; double hung sash windows with 6/6 lights. App. 1900-1910. Typical shotgun houses - significant as part of a potential N.R. district.
1 electronic record. 2 page scans [TIFF Format]. 1 image scans [TIFF, JPG]. 1 PDF/A files. 5 files. 98.0 MB (102,778,489 bytes).
Keywords: Lowndes County (Ga.); Valdosta (Ga.); Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.)